1988
DOI: 10.1007/bf00156441
|View full text |Cite
|
Sign up to set email alerts
|

Pupil size and the steady-state pattern reversal visual evoked cortical potential

Abstract: 30 eye-healthy subjects were being examined, with their pupils reacting, mydriatic or miotic. Their pattern reversal visual evoked cortical potentials (PRVECP's) were recorded under steady-state conditions. Test conditions allowed establishing a statistically significant influence of pupil size on the PRVECP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1989
1989
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 2 publications
0
10
0
Order By: Relevance
“…Past studies have investigated the influence of pupil size on the VEP to improve a diagnostic automated pupillometry device, and demonstrated that both extremely constricted and dilated pupils deteriorated the signal-to-noise ratio of pupillometry as compared to a normal pupil (Hawkes and Stow, 1981;Lovasik et al, 1985;Muller et al, 1988;Martins et al, 2003;Salim et al, 2010;Sabeti et al, 2011). The underlying mechanisms should include not only pupillary light reflex, but also non-visual factors such as arousal, attention, and cortical state, yet it is difficult to quantify each contribution in VEP.…”
Section: Evoked Response Vs Pupil Sizementioning
confidence: 96%
“…Past studies have investigated the influence of pupil size on the VEP to improve a diagnostic automated pupillometry device, and demonstrated that both extremely constricted and dilated pupils deteriorated the signal-to-noise ratio of pupillometry as compared to a normal pupil (Hawkes and Stow, 1981;Lovasik et al, 1985;Muller et al, 1988;Martins et al, 2003;Salim et al, 2010;Sabeti et al, 2011). The underlying mechanisms should include not only pupillary light reflex, but also non-visual factors such as arousal, attention, and cortical state, yet it is difficult to quantify each contribution in VEP.…”
Section: Evoked Response Vs Pupil Sizementioning
confidence: 96%
“…Pupil size has been recognized as an important variable when recording a visual evoked potential (VEP), as it determines the quantity of light entering the eye 1−4 . Full field pattern‐VEP studies showed a decrease in latency with increasing pupil diameter 1,2 .…”
Section: Introductionmentioning
confidence: 99%
“…found a small reduction in amplitude as the pupil dilated. The effect of spatial frequency on the relationship between pupil size and amplitude has been examined 3 . Pupil size was found to influence pattern VEP amplitude only at the highest tested frequency, where an inverse relationship was noted.…”
Section: Introductionmentioning
confidence: 99%
“…Advantages of icVEP compared with mfVEP include shorter test duration and more meticulous and detailed quantification of the SNR response through the use of multivariate statistical analysis. Muller et al [26] also reported a statistically significant influence of pupil size on steady-state pattern reversal visual evoked cortical potentials.…”
Section: Discussionmentioning
confidence: 94%